The enemy at home - O'Brien, Kevin, 1955- (Kensington Publishing Corp., 2023)
"1943, Seattle. While raging war reshapes the landscape of Europe, its impact is felt thousands of miles away too. Before the war, Nora Kinney was one of countless housewives and mothers in her comfortable Capitol Hill neighborhood. Now, with her doctor husband stationed in North Africa, Nora feels compelled to do more than tend her victory garden or help with scrap metal drives ... At the Boeing B-17 plant, Nora learns to wield a heavy riveting gun amid the deafening noise of the assembly line-a real-life counterpart to "Rosie the Riveter" in the recruitment posters. Yet while the country desperately needs their help, not everyone is happy about "all these women" taking over men's jobs. Nora worries that she is neglecting her children, especially her withdrawn teenage son. But amid this turmoil, a sinister tragedy occurs: One of Nora's coworkers is found strangled in her apartment, dressed in an apron, with a lipstick smile smeared on her face. It's the beginning of a terrifying pattern, as women war-plant workers like Nora are targeted throughout Seattle and murdered in the same ritualistic manner. And eclipsing Nora's fear for her safety is her secret, growing conviction that she and the killer are connected-and that the haven that was her home has become her own personal battlefield . . ."--